Derogatory wolf culling in France: evaluation of the effects on livestock depredation losses - Grente, Oksana; Duchamp, Christophe; Bauduin, Sarah; Chamaille-Jammes, Simon; Drouet-Hoguet, Nolwenn; Gimenez, Olivier (Naturae, 2023)
National audience The effectiveness of lethal removals of grey wolf (Canis lupus Linnaeus, 1758) in reducing predation on livestock has been debated, both in France and elsewhere where such measures are applied. In this article, we report on the results of a thesis conducted by Oksana Grente, under the direction of Office français de la Biodiversité (OFB) and Centre d’Écologie fonctionnelle et évolutive (CEFE-CNRS), who studied the effects of wolf culling on attacks on sheep in the French Alps. Two complementary approaches were adopted to answer this question. First, the data from the French administration which records attack reports, were analyzed by comparing the situations before and after culling. It was found that the effects of culling could be multiple and depended on the context in which the culling took place. The disparity in these results remains difficult to understand with the available data. In order to address the shortcomings of the analysis with the observed data on culling, a theoretical model was developed in which wolf predation behaviour was simulated under different assumptions, in order to improve our understanding of the interactions between wolves, flocks and derogatory culling. The simulations indicate that lethal control was effective in reducing depredation in contexts where livestock is protected and less vulnerable to predation than wild prey. The difficulty lies in defining, in the field, the pastoral and environmental contexts that govern predation behaviour and therefore the effects of derogatory culling. One solution would be to carry out local surveys within each set of pastoral areas belonging to the same depredation hotspot. The PhD thesis proposes a statistical methodology to identify these groups of pastures. This method allows to take into account the use of pastures by sheep, and thus the rate of exposure to the risk of depredation which differs among flocks. To conclude, the results of the thesis call for a contextualized management of attacks through culling, that ...